Nystatin and lidocaine pastilles for the local treatment of oral mucositis. (17th February 2017) - Silva, Filipa Cosme; Marto, Joana M.; Salgado, Ana; Machado, Paula; Silva, Alexandra N.; Almeida, António J.
Abstract: Oral mucositis (OM) is a common adverse reaction to radiotherapy and chemotherapy in oncology. Its treatment requires oral formulations that enhance therapy compliance, improve administration and ensure drug effectiveness. Solid dosage forms that act by slow dissolution, such as pastilles, are an effective alternative to mouthwashes, for their versatility, ease of administration and extended residence time in the oral cavity. The present work describes the development and stability studies of an innovative formulation of nystatin and lidocaine pastilles for the treatment of oral mucositis. Full pharmaceutical quality testing was carried out, including disintegration and dissolution testing, texture profile analysis, grittiness and an antifungal activity testing. A soft pastille formulation containing 0.25% lidocaine and 78, 000 IU nystatin was obtained, presenting suitable pharmaceutical characteristics, as a disintegration time of 17 ± 2 min, dissolution rate and microbiological and physicochemical for 30 days when stored at 2–8 °C under light protection. Palatability was also evaluated, being well accepted by a panel of 38 healthy volunteers. This formulation allows an accurate drug dosing by the prescriber, while enabling the patients to control the retention time of the drugs in the oral cavity and consequently manage their pain treatment.